ENVIRONMENTAL BUSINESS - ENTERPRISE MODELS (Economic journal of Lesya Ukrainka Volyn National University, 2024)
The purpose of the article is to identify the prerequisites for pro-environmental behavior of companies and to present the main business models of an enterprise that considers environmental responsibility as one of the priorities of activity in market conditions. It has been established that environmental responsibility is a factor affecting the development of the enterprise on a global, regional and local scale. Motives that mobilize companies to adopt pro-environmental positions include: increasing societal pressure to improve the quality of the environment, growing environmental demands of consumers, reducing the value of technologies and products that do not meet environmental standards, taking into account the requirements of the international market, including the EU market, strengthening requirements to environmental protection and increased costs due to failure to take measures to protect its resources and improve their operating conditions, changing the market position of enterprises that use pro-environmental management, expanding the scope of activity for profit and a favorable position on the market. It is proven that the pro-environmental orientation of the enterprise affects its business model, that is, a coordinated plan of action aimed at creating a strategy that meets the expectations of customers through the optimal use of resources and relationships. Two business models of enterprise behavior are distinguished: reactive, which means compliance with current legal requirements in the field of environmental protection, and proactive, which takes into account the environmental factor in the future development of the enterprise. It is substantiated that the proactive and effective model of social and environmental responsibility of business and the entrepreneurial model of social and environmental responsibility of business relate to the implementation of environmental goals and include economic and social goals. Both are based on the following assumptions: taking into account the provisions of sustainable development, creating a socially responsible corporate culture, implementing the concept of stakeholders, taking into account the natural environment as a "silent stakeholder", implementing the principles of CSR and the concept of environmental responsibility, taking them into account when creating the enterprise's business architecture.
Keywords: pro-environmental orientation of the enterprise, proactive model, reactive model, pro-effective model of social and environmental responsibility of business, entrepreneurial model of social and environmental responsibility of business, environmental responsibility.